Induced Abortion Provision Among a National Sample of Obstetrician–Gynecologists. Issue 3 (March 2019) - Grossman, Daniel; Grindlay, Kate; Altshuler, Anna L.; Schulkin, Jay
Abstract : OBJECTIVE: To estimate the proportion of obstetrician–gynecologists (ob-gyns) who provided induced abortion in the prior year, disaggregated by surgical and medication methods, and document barriers to provision of medication abortion. METHODS: In 2016–2017, we conducted a cross-sectional survey of a national sample of American College of Obstetricians and Gynecologists Fellows and Junior Fellows who were part of the Collaborative Ambulatory Research Network. We sent the survey by email, and mailed nonresponders paper surveys. We performed descriptive statistics, χ 2 tests, and logistic regression analyses. RESULTS: Sixty-seven percent (655/980) of Collaborative Ambulatory Research Network members responded. Ninety-nine percent reported seeing patients of reproductive age, and 72% reported having a patient in the prior year who needed or wanted an abortion. Among those seeing patients of reproductive age, 23.8% (95% CI 20.5%–27.4%) reported performing an induced abortion in the prior year; 10.4% provided surgical and medication abortion, 9.4% surgical only, and 4.0% medication only. In multivariable analysis, physicians practicing in the Midwest (adjusted odds ratio [AOR] 0.31, 95% CI 0.16–0.60) or South (AOR 0.22, 95% CI 0.11–0.42) had lower odds of provision compared with those practicing in the Northeast, whereas those practicing in an urban inner city (AOR 2.71, 95% CI 1.31–5.60) or urban non–inner-city area (AOR 2.89, 95% CI 1.48–5.64 vs midsize towns, rural areas, or military settings) had higher odds of provision. The most common reasons for not providing medication abortion were personal beliefs (34%) and practice restrictions (19%). Among those not providing medication abortion, 28% said they would if they could write a prescription for mifepristone. CONCLUSION: Compared with the previous national survey in 2008–2009, abortion provision may be increasing among practicing ob-gyns, although important geographic disparities persist. Few provide medication abortion, but uptake might increase if mifepristone could be prescribed. Abstract : One quarter of obstetrician–gynecologists provide induced abortion, with variation by geography and community type, but medication abortion provision might increase if physicians could prescribe the medications.